FLUXAPYROXAD IN THE ASIAN SOYBEAN RUST CONTROL IN THE CERRADO BIOME - Freitas, Rafael Menezes Silva de (2016)
The etiologic agent of the Asian soybean rust is the Phakopsora pachyrhizi, which causes a reduction in the photosynthetic leaf area and, consequently, in the crop yield. Chemical control is one of the main measures for its management. The objective of this work was to evaluate the efficacy and selectivity of the fluxapyroxad fungicide on controlling the Asian soybean rust, under the edaphoclimatic conditions of the Cerrado biome. The experiment was conducted in an area under no-tillage system, in the Agricultural Research Center, Rio Verde, Goias, Brazil, during the 2012/2013 crop season, using the cultivar NA7337. A randomized block experimental design was used, with twelve treatments and four replications. The treatments consisted of applications of fluxapyroxad (FX), pyraclostrobin (PT), epoxiconazole (EX) and metconazole (MZ). The average severity of the disease in the plants reached 37% in the Control. All treatments with fungicides differed from the Control. Treatments 9, 10, 11 and 12 provided the greatest rates of soybean rust control. The treatments 10, 11 and 12 had the highest thousand grain weights, and the yields of the treatments 2, 3 and 11, despite higher than the Control, were lower than the treatments 4, 5, 6, 7, 8, 9, 10 and 12, which had statistically equal yields. The increasing in yield, compared to the Control, ranged from 10.05% (pyraclostrobin, epoxiconazole + pyraclostrobin + mineral oil) to 30.55% (pyraclostrobin, pyraclostrobin + fluxapyroxad + mineral oil and pyraclostrobin + metconazole + mineral oil). The highest rates of soybean rust control were presented by fungicides containing fluxapyroxad.